Influence of physical and chemical agents on trimethylamine and total volatile bases of Oreochromis niloticus - Castro, Bruna Godoi [UNESP]; Velame, Marise Santiago [UNESP]; Haber Garcia, Lorena Natalino [UNESP]; Moraes, Gustavo Nunes de [UNESP]; Baldini, Eduardo Delbon [UNESP]; Possebon, Fabio Sossai [UNESP]; Almeida Nogueira Pinto, Jose Paes [UNESP]; Raghiante, Fernanda; Martins, Otavio Augusto [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2018)
The present work aims to evaluate the influence of physical and chemical agents on trimethylamine and total volatile bases of Oreochromis niloticus. Samples of Oreochromis niloticus from commercial establishments were analyzed. Three treatments (A, B and C) were carried out, which were influenced by physical agents (temperatures of 4 degrees C and 25 degrees C) and chemical (ammonium hydroxide). The treatments were analyzed on the first, fourth and seventh days after sample acquisition. The main results showed that treatments A, B and C did not present statistical differences (p>0.05) for trimethylamine in the analyzed periods and treatment A presented statistical difference (p<0.05) for total volatile bases in the analyzed periods and lower concentration compared to the other treatments (B and C) on the first day of analysis. We conclude that the chemical agent (ammonium hydroxide) (a) influenced the total volatile bases in the evaluated periods; and (b) showed low concentrations of total volatile bases compared to the other treatments on the first day of evaluation.
Keywords: Physical Agent; Chemical Agent; Total Volatile Bases; Trimethylamine